PEMASARAN PRODUK UKM MELALUI JARINGAN RETAIL BESAR - Yudha Hadian Nur; Lukman Muslimin (Buletin Ilmiah Litbang Perdagangan, 2009)
The modern retail industry has grown rapidly in Indonesia for the last decade. The business growth  on one side, it also caused tighter competition among suppliers in the industry in order to be able to access the modern retail networks, as well as the possibility of sacrificing the traditional retail, especially small and medium scale enterprises (SMEs). Although the government has created  regulatory framework that is aimed to maintain profitable business for both traditional and modern market, and to increase  the local business participation  in modern  retail through partnership  program, the issued that has been occurred  is that most  traditional  retailers have difficulties in expanding their market to modern  retails. By using the descriptive analisys, the research is carried  out to reqognize some terms and conditions  that has been determined by modern retails to their become supplier, the factor analisys that are to the profit margin  for both  modern and traditional retailers. Meanwhile Analytical Hierarchy Process (AHP) is used produce draft of policies and procedures mechanisms in order enhance small medium enterprises access to modern market.  Some recommendation from the research is increasing standard quality of local products and lessen the trading terms, specially that could bring disadvantage to the traditional retailers as stated in Presidential Decree No. 112/2007.